Cranial morphological diversity of early, middle, and late Holocene Brazilian groups: Implications for human dispersion in Brazil. Issue 4 (11th September 2014) - Hubbe, Mark; Okumura, Mercedes; Bernardo, Danilo V.; Neves, Walter A.
ABSTRACT The history of human occupation in Brazil dates to at least 14 kyr BP, and the country has the largest record of early human remains from the continent. Despite the importance and richness of Brazilian human skeletal collections, the biological relationships between groups and their implications for knowledge about human dispersion in the country have not been properly explored. Here, we present a comprehensive assessment of the morphological affinities of human groups from East‐Central, Coastal, Northeast, and South Brazil from distinct periods and test for the best dispersion scenarios to explain the observed diversity across time. Our results, based on multivariate assessments of shape and goodness of fit tests of dispersion and adaptation models, favor the idea that Brazil experienced at least two large dispersion waves. The first dispersive event brought the morphological pattern that characterize Late Pleistocene groups continent‐wide and that persisted among East‐Central Brazil groups until recently. Within the area covered by our samples, the second wave was probably restricted to the coast and is associated with a distinct morphological pattern. Inland and coastal populations apparently did not interact significantly during the Holocene, as there is no clear signal of admixture between groups sharing the two morphological patterns. However, these results cannot be extended to the interior part of the country (Amazonia and Central Brazil), given the lack of skeletal samples in these regions. Am J Phys Anthropol 155:546–558, 2014. © 2014 Wiley Periodicals, Inc.